A brief study on the implementation of transformers for track electrification. Issue 4 (2nd October 2019) - Viswanathan, Rajeswari
ABSTRACT: In the current state, the electric traction system is the cheapest and efficient medium for both personnel and material transportation. As electric locomotives are connected as loads, they introduce power quality problems due to their dynamic speed and load conditions. The power quality of these new high-capability swift-flying trains needs to be improved. In order to increase the power quality of systems, the transformers are designed. The objective of the work is to design an electric traction system that reduces the unsymmetrical voltages of electrification systems by using two different transformers in the Simulink environment.